Sensor Grid Middleware Metamodeling and Analysis - Srimathi Chandrasekaran; Eunmi Choi; Jemal H. Abawajy; Rajesh Natarajan (International Journal of Distributed Sensor Networks)
Sensor grid is a platform that combines wireless sensor networks and grid computing with the aim of exploiting the complementary advantages of the two systems. Proper integration of these distinct systems into effective, logically single platform is challenging. This paper presents an approach for practical sensor grid implementation and management. The proposed approach uses a metamodeling technique and performance analysis and tuning as well as a middleware infrastructure that enable practical sensor grid implementation and management. The paper presents our implementation and analysis of the sensor grid.